When you multiply two radicals with same index, you can take the radical once and multiply the numbers inside the radical.
Examples :
√a ⋅ √b = √(a ⋅ b)
3√a ⋅3√b = 3√(a ⋅ b)
In general,
n√a ⋅ n√b = n√(a ⋅ b)
Example 1 :
Evaluate :
(√6)(√6)
Solution :
= √6 ⋅ √6
= √(6 ⋅ 6)
= 6
Example 2 :
Evaluate :
(3√12)(√6)
Solution :
= 3√12 ⋅ √6
= 3√(12 ⋅ 6)
= 3√72
= 3√(6 ⋅ 6 ⋅ 2)
= 3(6√2)
= 18√2
Example 3 :
Evaluate :
√6(√3 + √12)
Solution :
= √6(√3 + √12)
= √6√3 + √6√12
= √(6 ⋅ 3) + √(6 ⋅ 12)
= √18 + √72
= √(3 ⋅ 3 ⋅ 2) + √(6 ⋅ 6 ⋅ 2)
= 3√2 + 6√2
= 9√2
Example 4 :
Evaluate :
(√2 + √7) (√5 - √6)
Solution :
= (√2 + √7) (√5 - √6)
= √2√5 + √2(-√6) + √7√5 + √7(-√6)
= √2√5 - √2√6) + √7√5 - √7√6
= √(2 ⋅ 5) - √(2 ⋅ 6) + √(7 ⋅ 5) - √(7 ⋅ 6)
= √10 - √12 + √35 - √42
= √10 - √(2 ⋅ 2 ⋅ 3) + √35 - √42
= √10 - 2√3 + √35 - √42
Example 5 :
Evaluate :
(2 - 3√5)(5 - √5)
Solution :
= (2 - 3√5)(5 - √5)
= 2(5) + 2(-√5) - 3√5(5) - 3√5(-√5)
= 10 - 2√5) - 15√5 + 3√(5 ⋅ 5)
= 10 - 17√5 + 3(5)
= 10 - 17√5 + 15
= 25 - 17√5
Example 6 :
Evaluate :
(5 + 4√3)(3 + √3)
Solution :
= (5 + 4√3) (3 + √3)
= 5(3) + 5(√3) + 4√3(3) + 4√3(√3)
= 15 + 5√3 + 12√3 + 4√(3 ⋅ 3)
= 15 + 17√3 + 4(3)
= 15 + 17√3 + 12
= 27 + 17√3
Example 7 :
Evaluate :
(5√24 + √3)(2 - √3)
Solution :
= (5√24 + √3)(2 - √3)
= (5√(2 ⋅ 2 ⋅ 2 ⋅ 3) + √3)(2 - √3)
= (10√(2 ⋅ 3) + √3)(2 - √3)
= (10√6 + √3)(2 - √3)
= 10√6(2) + 10√6(-√3) + √3(2) + √3(-√3)
= 20√6 - 10√(6 ⋅ 3) + 2√3 - √(3 ⋅ 3)
= 20√6 - 10√(2 ⋅ 3 ⋅ 3) + 2√3 - 3
= 20√6 - 10(3√(2) + 2√3 - 3
= 20√6 - 30√2 + 2√3 - 3
Example 8 :
Evaluate :
(-3√3x + 4)(√3x - 5)
Solution :
= (-3√3x + 4)(√3x - 5)
= -3√3x(√3x) - 3√3x(-5) + 4(√3x) + 4(-5)
= -3√(3x ⋅ 3x) + 15√3x + 4√3x - 20
= -3(3x) + 19√3x - 20
= -9x + 19√3x - 20
Example 9 :
Evaluate :
(-4√28x)(√7x3)
Solution :
= (-4√28x)(√7x3)
= -4√(28x ⋅ 7x3)
= -4√(28x ⋅ 7x3)
= -4√(7 ⋅ 2 ⋅ 2 ⋅ 7 ⋅ x2 ⋅ x2)
= -4(7 ⋅ 2 ⋅ x2)
= -4(14x2)
= -56x2
Example 10 :
Evaluate :
(√15x2)(√10x3)
Solution :
= (√15x2)(√10x3)
= √(15x2 ⋅ 10x3)
= √(5 ⋅ 3 ⋅ 2 ⋅ 5 ⋅ x2 ⋅ x2 ⋅ x)
= 5x2√(3 ⋅ 2 ⋅ x)
= 5x2√6x
Example 11 :
Evaluate :
Solution :
= (3√24)(3√9)
= 3√(24 ⋅ 9)
= 3√(2 ⋅ 2 ⋅ 2 ⋅ 3 ⋅ 3 ⋅ 3)
= 2 ⋅ 3
= 6
Example 12 :
Evaluate :
Solution :
= (3√250x3)(3√4y6)
= 3√(250x3 ⋅ 4y6)
= 3√(1000x3y6)
= 3√(10 ⋅ 10 ⋅ 10 ⋅ x ⋅ x ⋅ x ⋅ y2 ⋅ y2 ⋅ y2)
= 10xy2
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 04, 25 08:16 AM
Feb 04, 25 08:15 AM
Feb 04, 25 08:11 AM